Exploring the views of GPs, people with dementia and their carers on assistive technology: a qualitative study. Issue 5 (13th May 2016) - Newton, Lisa; Dickinson, Claire; Gibson, Grant; Brittain, Katie; Robinson, Louise
Abstract : Objectives: To explore the views and experiences of people with dementia, their family carers and general practitioners (GPs) on their knowledge and experience of accessing information about, and use of, assistive technology (AT) in dementia care. Design: Qualitative methods with semistructured interviews and thematic analysis. Participants: 56 participants comprising 17 GPs, 13 people with dementia and 26 family carers. Setting: Community care settings in the North East of England. Results: 4 main themes emerged: awareness and experience of AT; accessing information on AT; roles and responsibilities in the current care system and the future commissioning of AT services. All participants had practical experience of witnessing AT being used in practice. For people with dementia and their families, knowledge was usually gained from personal experience rather than from health and social care professionals. For GPs, knowledge was largely gained through experiential, patient-led learning. All groups acknowledged the important role of the voluntary sector but agreed a need for clear information pathways for AT; such pathways were perceived to be essential to both service providers and service commissioners. Conclusions: People with dementia and their family carers appear to be mainly responsible for driving a gradual increase in both awareness and the use of AT in dementia care. GPs should be equipped with the relevant knowledge to ensure families living with dementia receive appropriate information and support to enable them to live independently for as long as possible. There is an urgent need to simplify current complex community care pathways; as demonstrated in other chronic health conditions, a single point of access and a named lead professional may improve future care.